DEVELOPMENT OF SETS-BASED WITH OUTDOOR LEARNING-METHOD Of STUDENT WORKSHEET TO ADVANCE ENVIRONMENTAL SCIENCE PROCESS SKILL AND ATTITUDE IN A VIIth GRADE HIGH SCHOOL STUDENTS - Claudhia Anandhi Maya; Insih Wilujeng; Purwanti Widhy Hastuti (Journal of Science Education Research, 2017)
The aims of this research were to (1) produce SETS-based with outdoor learning-method of student worksheet which is valid to advance students ' science process skill and environmental attitude in a VIIth grade high school students based on the validator, (2) know the student respond on SETS-based with outdoor learning-method of student worksheet (3) know the advancement of students ' science process skill after using the color SETS-based with outdoor learning-method of student worksheets and (4) know the advancement of students ' environmental attitude after using the color SETS-based with outdoor learning-method of student worksheets. The sample of this study included 30 students of SMP E class VII 1 Paliyan. Research of the model that is being conducted is 4 d model comprises define, design, develop, and disseminate. According to results:: (1) The student worksheet developed was valid to advance students ' science process skill and environmental attitude in a VIIth grade high school students according to the validator, with very good category. (2) Student responses on the developed worksheets were very good. (3) Developed the worksheet can advance students science process skill which is shown by a good percentage, medium gains, and suppotted by significant result of paired sample t-test. (3) Developed the worksheet can advance students science process skill which is shown by a good percentage, medium gains, and suppotted by significant result of paired sample t-test.